Leading From the Front : The Autobiography - Dannatt, Richard, 1950- (London Bantam Press, 2010)
As Chief of the General Staff, Sir Richard Dannatt was in overall command of the British army for the three years from 2006. This period saw some of the fiercest fighting yet in Afghanistan, and new and increased pressures and expectation placed on the army.
Include Index, Epilogue and Illustrations
Keywords: Military policy